2009
DOI: 10.1021/jp9079603
|View full text |Cite
|
Sign up to set email alerts
|

Short-Range Structure of Invert Glasses along the Pseudo-Binary Join MgSiO3−Mg2SiO4: Results from 29Si and 25Mg MAS NMR Spectroscopy

Abstract: The short-range structure of "invert" glasses along the pseudobinary join MgSiO(3)-Mg(2)SiO(4) has been studied using (29)Si and (25)Mg MAS NMR spectroscopy. The results indicate a progressive compositional evolution in Q speciation that approximately follows a statistical distribution. The Mg(2)SiO(4) glass shows an abrupt deviation from this trend with the presence of nearly 40% of the Si atoms as (Si(2)O(7))(6-) dimers, i.e., Q(1) species. Mg(2+) ions are present in predominantly octahedral coordination in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
100
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 20 publications
14
100
3
Order By: Relevance
“…In the case of MgSiO 3 glass, the RMC model suggests that MgO 4 is the major unit, which is consistent with the coordination number derived from a combination of X-ray and neutron diffraction data (16,17). However, the result of two recent NMR studies (14,15) suggests that MgO 6 octahedra are the primary units in both MgSiO 3 glass and Mg 2 SiO 4 glass (although 5-fold sites could not be ruled out). Attempts to include large fractions of MgO 6 polyhedra in our RMC simulations failed, even if the coordination number was calculated out to large distances i.e., 3.0 Å.…”
Section: Resultssupporting
confidence: 69%
See 2 more Smart Citations
“…In the case of MgSiO 3 glass, the RMC model suggests that MgO 4 is the major unit, which is consistent with the coordination number derived from a combination of X-ray and neutron diffraction data (16,17). However, the result of two recent NMR studies (14,15) suggests that MgO 6 octahedra are the primary units in both MgSiO 3 glass and Mg 2 SiO 4 glass (although 5-fold sites could not be ruled out). Attempts to include large fractions of MgO 6 polyhedra in our RMC simulations failed, even if the coordination number was calculated out to large distances i.e., 3.0 Å.…”
Section: Resultssupporting
confidence: 69%
“…The X-ray total structure factors SðQÞ together with the experimental data (40) The DFT calculations explain the discrepancy between the NMR and diffraction results, because NMR probes chemical shifts which are very sensitive to the electronic environment of the nuclei, while diffraction is a direct probe of the average coordination number through known neutron scattering lengths or the number of electrons surrounding an atom (provided the partial functions are known). Previous studies (14,15) concluded that for MgSiO 3 and Mg 2 SiO 4 glasses, the NMR shifts are in line with the octahedral crystalline environment, although in this (38). The structural glass model presented here at ambient pressures does however explain the low viscosity of highly mobile ultramafic lavas.…”
Section: Resultscontrasting
confidence: 41%
See 1 more Smart Citation
“…Sen et al (2009) have determined the relative proportion of Q i species in 9 glasses from a series of (MgO) y (SiO 2 ) 100−y glasses with y in the range 50-66.7 (y=50, 60, 66.7 correspond to x=0.5, 0.40, 0.33 in the notation adopted here). The samples X35, X40 and X50A were synthesized by the same team using the same technique as the study of Sen et al (2009) species in respective proportions of about 50-60 and 50-40%. As expected, the X35 sample close to the forsterite composition, is less polymerized than the the X50A sample, of enstatite composition, the X40 being intermediate.…”
Section: Samples Synthesis and Characterizationmentioning
confidence: 99%
“…Besides the use of large volume samples, there are also other ''brute force'' approaches frequently used since the earlier reports of solid-state 25 Mg NMR, including isotopic enrichment and the use of magnetic fields as strong as possible. 6,37,39,42,43,[45][46][47][48][49][50][51][52] There is no doubt that the increase in the number of reports involving solid-state 25 Mg NMR has been driven by the wider availability of high-field magnets (e.g. !14.1T).…”
Section: Nmr Interactionsmentioning
confidence: 99%